Arctic Resilience Action Framework; cooperating for a More Resilient and Prosperous Arctic Region - ARAF Chair (Arctic Council Secretariat, 2016)
The Arctic Resilience Action Framework (ARAF) provides a common set of guiding principles and priorities for Action.